2016
DOI: 10.1051/matecconf/20168002009
|View full text |Cite
|
Sign up to set email alerts
|

Study on micro hydro-mechanical deep drawing using finite element method

Abstract: Abstract. A numerical model was established to investigate the micro hydro-mechanical deep drawing process of austenitic stainless steel 304 foil (0.05 mm thickness). Due to the miniaturisation of the specimen size, the effect of grain size, gap distance and radial pressure during drawing process could be prominent. The results indicate that the appropriate radial pressure and gap distance could improve the limit drawing ratio (LDR) of manufactured cylindrical cups by reducing the friction resistance. The maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Their research results showed that size effects were noticeable and significant when the thickness of the foils was equal to or less than 100 µm, and foil thickness, grain size and ratio of foil thickness (T) to grain size (D) affected significantly the value of LDR of ASS 304 foils. Ma et al [10] established a numerical model to investigate the MDD with radial pressure, and found that appropriate radial pressure and gap distance could improve the LDR of drawn ASS 304 circular cups by reducing the friction resistance. Huang et al [11] investigated the MDD with assistance of ultrasonic vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Their research results showed that size effects were noticeable and significant when the thickness of the foils was equal to or less than 100 µm, and foil thickness, grain size and ratio of foil thickness (T) to grain size (D) affected significantly the value of LDR of ASS 304 foils. Ma et al [10] established a numerical model to investigate the MDD with radial pressure, and found that appropriate radial pressure and gap distance could improve the LDR of drawn ASS 304 circular cups by reducing the friction resistance. Huang et al [11] investigated the MDD with assistance of ultrasonic vibration.…”
Section: Introductionmentioning
confidence: 99%